The Recent Developments and Emerging Trends in Labour-Management Relations in the U.S.A. and Canada - Jain, Hem (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1965)
Collective bargaining has gone through three different stages in US evolution: organizational, containment and accomodation. However, in the last few years, pressures and complexities in collective bargaining have threatened the very existence of this institution.In this article the author explains and analyses recent developments in labour relations, more particularly the creation of committees in large corporations in order to provide for a joint continuing study of the problems and issues of mutual interest to both parties.